2019
DOI: 10.1111/nicc.12413
|View full text |Cite
|
Sign up to set email alerts
|

Stress and uncertainty in parents of children with tracheobronchial malacia and stenosis

Abstract: Background: An increasing number of children are undergoing flexible bronchoscopy because of tracheobronchial malacia and stenosis, but there is little research related to their parents' stress and uncertainty. Aim: To explore and identify risk factors associated with stress and uncertainty among Taiwanese parents of children with tracheobronchial malacia and tracheabronchostenosis in a paediatric intensive care unit. Methods: A cross-sectional study design was implemented using two psychometric scales: Parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…For those who are accustomed to adopting negative coping styles, information support in terms of disease diagnosis and treatment, prognosis, and care should be improved [ 13 ], and effective preoperative guidance and treatment should be provided. Guide [ 33 ] promoted the formation of an effective positive coping style, and those who tend to use positive coping styles should focus on the exercise of their personal abilities, tap their own potential and strength, and reduce disease uncertainty. Huang Zhirong et al [ 34 ] found in a study of parents of premature infants that family empowerment programs can reduce illness uncertainty in parents of premature infants and improve family care readiness and postdischarge coping abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For those who are accustomed to adopting negative coping styles, information support in terms of disease diagnosis and treatment, prognosis, and care should be improved [ 13 ], and effective preoperative guidance and treatment should be provided. Guide [ 33 ] promoted the formation of an effective positive coping style, and those who tend to use positive coping styles should focus on the exercise of their personal abilities, tap their own potential and strength, and reduce disease uncertainty. Huang Zhirong et al [ 34 ] found in a study of parents of premature infants that family empowerment programs can reduce illness uncertainty in parents of premature infants and improve family care readiness and postdischarge coping abilities.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Ho et al . () undertook a cross‐sectional survey with 90 parents of 51 children who were undergoing a bronchoscopy because of tracheobronchial malacia and tracheobronchosis. Using two scales, the Parental Stress index and Parents perception of Uncertainty scale , data were collected by the investigators or via postal services with a 100% response rate.…”
mentioning
confidence: 99%